Incidents in the life of a slave girl : Written by herself - Jacobs, Harriet (Bedford series in history and culture, 2010)
Examining the first- and best-known female account of life under, and escape from, slavery, Incidents in the Life of A Slave Girl, Written by Herself recounts Harriet Jacobs' story and shows how she used the written word to liberate herself and promote the end of slavery by inspiring sympathy.